Design of Potassium‐Selective Mixed Ion/Electron Conducting Polymers. Issue 12 (18th June 2020) - Villarroel Marquez, Ariana; Salinas, Gerardo; Abarkan, Myriam; Idir, Maël; Brochon, Cyril; Hadziioannou, Georges; Raoux, Matthieu; Kuhn, Alexander; Lang, Jochen; Cloutet, Eric
Abstract : Back Cover : In article 2000134, Eric Cloutet and co‐workers integrate potassium (K + ) selectivity into a poly(3, 4‐ethylenedioxythiophene) (PEDOT)‐based ink using a chemical design approach of the associated polyelectrolyte counterpart. Structural and electrochemical characterizations revealed significant selectivity for K + over Na + in this biocompatible material.